“I Didn’t Tell Anyone Because I Was Very Afraid”: Girls’ Experiences of Menstruation in Contemporary Ethiopia - Smiles, Dana (Womens Reprod Health (Phila), 2017)
Menstrual health is central to girls’ wellbeing, and is connected to their rights to health, education, safety, non-discrimination, and autonomy. This article investigates girls’ experiences of menstruation in present-day Ethiopia. Results, based on data collected from 120 girls in two regions, illustrate the challenges associated with menstruation, including menstrual taboos and cultural beliefs surrounding menstruation, myths about menstruation and sex, and restrictive social expectations related to marriage, and interpersonal interaction. These challenges diminish girls’ health, education, safety, and autonomy, and in so doing, underscore the relevance of menstrual health to rights’ agendas that seek to advance girls’ wellbeing.